Primary Care Shortage in Medically Underserved and Health Provider Shortage Areas: Lessons from Delaware, USA - Srikrishna Varun Malayala; Deepa Vasireddy; Paavani Atluri; Ram Sanjeev Alur (SAGE Publishing, 2021)
Objective: To examine the reasons contributing to the physician shortage in the country's medically underserved areas using the state of Delaware as a focus state. Method: A literature review regarding the shortage of physicians with data compilation from Delaware Department of Public Health (DPH) and Delaware Health and Social services (DHSS) was performed. A review of the "Conrad 30 J1 VISA waiver program," the most important and primary supplier of physicians to underserved areas of the state was performed. A survey interviewing the physicians recruited through this program to identify any challenges faced by them was designed and conducted. Results: The number of primary care physicians providing direct patient care in Delaware in 2018 had declined about 6% from 2013. The average wait time to see a PCP was 8.2 days in 1998 as compared to 23.5 days in 2018. Forty-six percent of physicians serving in HPSAs in Delaware are IMGs recruited through the J1 VISA waiver program. Eighty percent of these IMGs are actively considering leaving the United States due to anxieties around physician immigration policies, mainly "Immigration backlog." Conclusion: The existing programs to recruit physicians to underserved areas seem to be inadequate. The state and the hospital systems should be able to utilize the J1 program to its full potential and focus on retaining these physicians after their assigned services. As the challenges of IMGs continue to worsen every day; the medical societies, hospitals, the state and federal government should advocate for policies that resolve these challenges.